2000
DOI: 10.1161/01.cir.101.22.2586
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Patterns of Dystrophin Organization in Myocyte Sarcolemma and Transverse Tubules of Normal and Diseased Human Myocardium

Abstract: Background-Genetic mutations of dystrophin and associated glycoproteins underlie cell degeneration in several inherited cardiomyopathies, although the precise physiological role of these proteins remains under discussion. We studied the distribution of dystrophin in relation to the force-transducing vinculin-rich costameres in left ventricular cardiomyocytes from normal and failing human hearts to further elucidate the function of this protein complex. Methods and Results-Single-and double-label immunoconfocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 36 publications
4
90
1
2
Order By: Relevance
“…The fact that they only occur in CMs in the border zone of infarcted myocardium and are always surrounded by fibrotic scar tissue suggests a mutual relation. Enlarged T-tubules running parallel to the longitudinal axis of the CM's and morphologically resembling the vacuoles seen in our study have been described in human left ventricular tissue from end-stage heart failure secondary to dilated cardiomyopathy [21]. Guinea pigs treated with an overload of volatile anaesthetics have been reported to show dilatations of the T-tubules [22], and dilatation of T-tubules through excessive activation of Na + -K + -ATPase from the sarcoplasmic side of the T-tubule membrane has been described in transected rat soleus muscle [23].…”
Section: Discussionsupporting
confidence: 83%
“…The fact that they only occur in CMs in the border zone of infarcted myocardium and are always surrounded by fibrotic scar tissue suggests a mutual relation. Enlarged T-tubules running parallel to the longitudinal axis of the CM's and morphologically resembling the vacuoles seen in our study have been described in human left ventricular tissue from end-stage heart failure secondary to dilated cardiomyopathy [21]. Guinea pigs treated with an overload of volatile anaesthetics have been reported to show dilatations of the T-tubules [22], and dilatation of T-tubules through excessive activation of Na + -K + -ATPase from the sarcoplasmic side of the T-tubule membrane has been described in transected rat soleus muscle [23].…”
Section: Discussionsupporting
confidence: 83%
“…Recently, this adhesion system was reported to be important in heart muscle function as well, and mutations in these molecules may cause cardiomyopathies. 18 Our results of the strongest expression of both ␣-and ␤-dystroglycan in combined therapy group showed that cardiomyoplasty combined with HGF gene transfection induced sufficient expression levels of another important cell adhesion molecules for cardiomyocytes. Laminin is one of the bestdescribed molecules comprising the extracellular matrix proteins and is the main component of the basement membrane.…”
Section: Discussionmentioning
confidence: 61%
“…4 The PDZ domain of syntrophin binds to the last 3 C-terminal residues of Na v 1.5 (Ser-Ile-Val, SIV), a PDZ-domain binding motif that mediates the interaction with dystrophin and other proteins of the DMC. 2 Interestingly, dystrophin has been shown to be absent from the intercalated discs of human 6 and rat 7 cardiac cells, suggesting that the Na v 1.5 channels present at these locations may interact with other regulatory or anchoring proteins.…”
mentioning
confidence: 99%